2018
DOI: 10.1007/s13346-018-00597-9
|View full text |Cite
|
Sign up to set email alerts
|

Albumin nano-encapsulation of caffeic acid phenethyl ester and piceatannol potentiated its ability to modulate HIF and NF-kB pathways and improves therapeutic outcome in experimental colitis

Abstract: Hypoxia inducible factor and nuclear factor-kappa beta pathways have been proposed as therapeutic targets for several inflammatory diseases. Caffeic acid phenethyl ester (CAPE) and piceatannol (PIC) are natural anti-inflammatory compounds; however, poor bioavailability and limited understanding of biomolecular mechanistic limits its clinical use. The aims of this study are to enhance bioavailability and investigate their impact on nuclear p65 and HIF-1α for the first time in experimental colitis.Dextran sulpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…This difference is useful in its spectrofluorometric analysis because this amino acid is the main residue responsible for the protein's intrinsic fluorescence [37][38][39]. Due to its biocompatibility, biodegradable, non-toxic, and non-immunogenic features, it has been proposed that BSA can offer a suitable nanocarrier system for drug delivery [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…This difference is useful in its spectrofluorometric analysis because this amino acid is the main residue responsible for the protein's intrinsic fluorescence [37][38][39]. Due to its biocompatibility, biodegradable, non-toxic, and non-immunogenic features, it has been proposed that BSA can offer a suitable nanocarrier system for drug delivery [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al reported that CAPE can suppress inflammation-induced MPO activity and proinflammatory cytokine production and can enhance epithelial barrier function in experimental colitis (10). Some recent studies also demonstrated that CAPE has a protective effect on colitis (33,34). However, it remains unknown whether CAPE can inhibit CAC and what the underlying mechanism is.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main limitations of CAPE are associated with its low water solubility and instability in physiological media. The incorporation of CAPE in appropriate drug delivery systems could overcome these limitations . For instance, Wadhwa et al .…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of CAPE in appropriate drug delivery systems could overcome these limitations. 29,30 For instance, Wadhwa et al 31 reported that the complexation of CAPE with gamma cyclodextrin might avoid its degradation in culture medium and lead to a higher anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%